The Role of Inhibitory Control in Second Language Phonological Processing. Issue 4 (1st February 2016) - Darcy, Isabelle; Mora, Joan C.; Daidone, Danielle
Abstract: This study investigated the role of inhibition in second language (L2) learners' phonological processing. Participants were Spanish learners of L2 English and American learners of L2 Spanish. We measured inhibition through a retrieval‐induced inhibition task. Accuracy of phonological representations (perception and production) was assessed through a speeded ABX categorization task and a delayed sentence repetition task. We used a measure of L2 vocabulary size to tease out L2 proficiency effects. Higher inhibitory control was related to lower error rate in segmental perception. Inhibition was also related to consonant but not to vowel production accuracy. These results suggest a potential role for inhibition in L2 phonological acquisition, with inhibition enhancing the processing of phonologically relevant acoustic information in the L2 input, which in turn might lead to more accurate L2 phonological representations. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris‐database.org . Learnmore about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki